2011
DOI: 10.1073/pnas.1105430108
|View full text |Cite
|
Sign up to set email alerts
|

Microbe domestication and the identification of the wild genetic stock of lager-brewing yeast

Abstract: Domestication of plants and animals promoted humanity's transition from nomadic to sedentary lifestyles, demographic expansion, and the emergence of civilizations. In contrast to the well-documented successes of crop and livestock breeding, processes of microbe domestication remain obscure, despite the importance of microbes to the production of food, beverages, and biofuels. Lager-beer, first brewed in the 15th century, employs an allotetraploid hybrid yeast, Saccharomyces pastorianus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
719
4
13

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 590 publications
(784 citation statements)
references
References 37 publications
19
719
4
13
Order By: Relevance
“…This phenomenon could be another explanation for the shifted geographical distributions of S. cerevisiae and S. paradoxus [20], as it was previously shown that they have contrasted tolerance to freeze-thaw cycles [27]. Additional evidence for the prominent role of temperature on budding yeast distribution was found in Saccharomyces eubayanus, a cold-adapted yeast that has only been reported in Patagonian forests, where climate is comparable with that of northeastern North America [35]. rspb.royalsocietypublishing.org Proc.…”
Section: Discussionmentioning
confidence: 85%
“…This phenomenon could be another explanation for the shifted geographical distributions of S. cerevisiae and S. paradoxus [20], as it was previously shown that they have contrasted tolerance to freeze-thaw cycles [27]. Additional evidence for the prominent role of temperature on budding yeast distribution was found in Saccharomyces eubayanus, a cold-adapted yeast that has only been reported in Patagonian forests, where climate is comparable with that of northeastern North America [35]. rspb.royalsocietypublishing.org Proc.…”
Section: Discussionmentioning
confidence: 85%
“…These results suggest that they are hybrid strains of S. cerevisiae and S. eubayanus. The hybrid origin of bottom brewing and wine yeast is often described in the literature (Bing et al, 2014, Libkind et al;Sipiczski, 2008 (Bing et al, 2014;Libkind et al, 2011;Sipiczski, 2008). U typového kmene S. pastorianus a S. pastorianus NCYC 396 došlo k amplifikaci pouze fragmentu o velikosti 228 bp, který je charakteristický pro S. eubayanus.…”
Section: ■ ■ 3 Results and Discussionmentioning
confidence: 99%
“…nov. 44 . Lager strains possess FLO genes derived from both their parents, and so have an even larger number and greater diversity of FLO genes in their genomes than ale (S. cerevisiae) strains.…”
Section: Flo Genotypes and Phenotypes In Brewer's Yeast Strainsmentioning
confidence: 99%